Assessment of the pregnancy rates using sequential day 3 and day 5 embryo transfer in IVF/ ICSI patients - Agrawal, Priti; Agrawal, Rishi; Lobo, Anandi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To assess the pregnancy rates using sequential day 3 and day 5 embryo transfer in IVF/ ICSI patients. Methods: This prospective study was conducted in Aarogya Hospital and test tube baby Centre, Raipur from 1st January 2013 to 30th November 2019. Total 100 patients undergoing IVF/ICSI in the study period were offered sequential transfer. Results: Our fertilization rates were 80% with 85.7% grade I embryos on day 3. Blastocyst formation rate was 71.42%. Cycle cancellation rates were nil. Clinical pregnancy rates per retrieval cycle were 50% and implantation rates were 24% with acceptable multiple pregnancy rates of 12%. Conclusions: We advocate that this technique is useful in all patients having good quality embryos in adequate number for double transfer as this optimizes the chance of selection of the most viable embryo for transfer which is probably the key for a successful IVF program.